2014
DOI: 10.1111/jce.12540
|View full text |Cite
|
Sign up to set email alerts
|

Probucol Prevents Atrial Remodeling by Inhibiting Oxidative Stress and TNF‐α/NF‐κB/TGF‐β Signal Transduction Pathway in Alloxan‐Induced Diabetic Rabbits

Abstract: Probucol prevents atrial remodeling and suppresses AF development in alloxan-induced diabetic rabbits. Its inhibitory effects on oxidative stress, NF-κB, TGF-β, and TNF-α overexpression may contribute to its antiremodeling effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 37 publications
4
50
0
Order By: Relevance
“…Autonomic dysfunction in DM patients can be caused by hyperglycemia‐mediated pathways such as formation of advanced glycation end products (AGEs), elevated oxidative or nitrosative stress with increased production of free radicals 19. Our previous work has reported that in the diabetic atria, electrical remodeling took the form of characterized by conduction slowing, increased AERP dispersion and prolonged action potential duration, in an absence of frequency‐dependent shortening of action potential duration, and increased amplitude of action potential duration alternans 21, 26. These would be expected to predispose to re‐entrant arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Autonomic dysfunction in DM patients can be caused by hyperglycemia‐mediated pathways such as formation of advanced glycation end products (AGEs), elevated oxidative or nitrosative stress with increased production of free radicals 19. Our previous work has reported that in the diabetic atria, electrical remodeling took the form of characterized by conduction slowing, increased AERP dispersion and prolonged action potential duration, in an absence of frequency‐dependent shortening of action potential duration, and increased amplitude of action potential duration alternans 21, 26. These would be expected to predispose to re‐entrant arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the serum concentrations of inflammatory cytokines (CRP, IL-6, IL-18, and TNF-α) are markedly lower in probucol-treated atherosclerotic rabbits [24] . The expression of TNF-α, TGF-β, and HSP70 is also significantly downregulated by probucol treatment in alloxaninduced diabetic rabbits [23] . Consistent with these reports, our findings provide evidence that treatment with probucol significantly reduced IL-1β and IL-6 production in addition to IL-1β and IL-6 gene expression in LPS-activated microglial BV2 cells (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the identification of novel agents that regulate neuroinflammation by inhibiting microglial activation is regarded as a significant strategy for the treatment of ischemic stroke. Several animal studies have demonstrated that probucol exerts beneficial effects via anti-inflammation mechanisms in aging mice [19,20] , focal cerebral ischemic mice [8,9] , heart failure rats [21,22] , diabetic rabbits [23] and atherosclerotic rabbits [24] . Probucol has also been demonstrated to prevent atherogenesis via the induction of the anti-inflammatory enzyme heme oxygenase-1 independently of lipid oxidation and cholesterol reduction in models of atherosclerosis, restenosis and type 2 diabetes [32] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, our data indicate that carbatonides might have a potential as drugs intended to treat DM complications. KEY WORDS: 1,4-dihydropyridine derivatives; diabetes mellitus; DNA damage; free radical scavengers; nitric oxide synthases New remedies for treatment of type one diabetes mellitus (T1DM) complications are sought among compounds with antioxidant activities (1,2). Following this logic, we have chosen some representatives of group of 1,4-dihydropyridine (1,4-DHP) derivatives synthesised in the Latvian Institute of Organic Synthesis (see Table 1 for structures).…”
mentioning
confidence: 99%